English English - Sri Adelila Sari; Jasmidi Jasmidi; Siti Rahmah; Kana Saputra S; Seget Tartiyoso; Bambang Suseno; Catur Kurniawan; Nadya Ulfa; Mhd. Fadhillah; Sahrul Ramadhan (LPPI UMN AL WASHLIYAH, 2024)
The revitalization of the SMK curriculum projects serves that students are not only ready to work but also be able to create jobs through entrepreneurship. SMK Students are provided additional hours of entrepreneurship coursework in order to foster creativity, innovation, and an entrepreneurial mindset among students. Furthermore, students are also required to possess a social entrepreneurial mindset, which encompasses a business development perspective that takes into account social, economic, environmental, and health factors. In this program, students are given training in making soap from used cooking oil. Used cooking oil is a waste that has promising business prospects. Appropriate processing of used cooking oil can yield valuable products that satisfy the needs of the community. As a result of this training, up to 97% of students have acquired greater understanding regarding the hazards and advantages associated with used cooking oil. Students possess advanced skills in producing soap products using used cooking oil. Furthermore, students develop a greater awareness regarding health and the environment.